2009
DOI: 10.1213/ane.0b013e3181a2a696
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Perioperative Red Blood Cell Transfusions and Decreased Long-Term Survival After Cardiac Surgery

Abstract: Exposure to 1 or 2 U of RBCs was associated with a 16% increased hazard of decreased survival after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
144
3
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(158 citation statements)
references
References 22 publications
7
144
3
4
Order By: Relevance
“…This is of much importance in surgeries performed in Jehova's Witnesses [8]. Several studies have shown that any amount greater than 1 unit of PRBC transfused, regardless of the procedure performed, results in decreased life expectancy of the patient [9][10][11]. In contrast to our study, other publications compared standard CPB with the system in which low crystalloid filling was used, and the postoperative day 1 drain output was comparable in both groups [12].…”
Section: Discussioncontrasting
confidence: 56%
“…This is of much importance in surgeries performed in Jehova's Witnesses [8]. Several studies have shown that any amount greater than 1 unit of PRBC transfused, regardless of the procedure performed, results in decreased life expectancy of the patient [9][10][11]. In contrast to our study, other publications compared standard CPB with the system in which low crystalloid filling was used, and the postoperative day 1 drain output was comparable in both groups [12].…”
Section: Discussioncontrasting
confidence: 56%
“…Blood transfusions after CABG have commonly been associated with increased long-term mortality (1)(2)(3)(4)(5)(6)(7)(8) as has CABG combined with AVR (9). We reached different results in a CABG population, where we extended the number of risk-factors entered in the survival analysis and did not find any association between transfusion of RBC and long-term survival in patients only undergoing CABG (10).…”
Section: Introductionmentioning
confidence: 87%
“…37 Observational studies have found higher postoperative mortality rates in transfused patients undergoing cardiac surgery compared with those who were not transfused, even after adjustment for other risk factors. 38 Randomized controlled trials (RCTs) in patients undergoing cardiac surgery have shown that white blood cell (WBC)-reduced blood products carry a lower mortality risk than non-WBC-reduced products. 23 However, this has not been observed after other types of surgery, and this issue is not resolved.…”
Section: Transfusion and Preoperative Anaemiamentioning
confidence: 99%